EDUCATING ZAKAT CALCULATION OF GOLD JEWELRY THROUGH THE MALAYSIAN ZAKAT INSTITUTION WEBSITE - Makhsin, Mardzelah; Ismail, Nor Hasimah; Narawi, Sawan Mohammad Syawal; Othman, Azizah; Ilias, Mohamad Fadhli bin (CENTRAL ASIA AND THE CAUCASUS, 2024)
The duty of zakat for jewelries or gold ornaments has sparked discussion among scholars. Most of the scholars think that it is not mandatory for zakat, but any individuals whose use exceeds the 'uruf rate, then it is mandatory for zakat. The zakat of jewelry has made 'uruf or local customary law as the basis of measurement. Most states in Malaysia have applied this opinion and the rate has also been issued according to their respective states. Therefore, the setting of zakat rate for gold jewelry is determined by the state zakat institution with the consent of the mufti in their respective states and is applicable only to the people of that state. The purpose of this study was to look at the websites of state zakat institutions in Malaysia, particularly related to gold jewelry zakat. To obtain the data needed in this study, a qualitative method was adopted by analyzing the documents obtained from each website of the zakat institutions in Malaysia. The study found that the highest rate of gold jewelry is set by the state of Terengganu at 850 grams. Meanwhile, the least tariff rate is set by the state of Sarawak at 90 grams. However, there are also states that do not set tariffs such as the states of Perlis and Kelantan. This is because the state of Perlis agrees that if the gold jewelry exceeds 85 grams, zakat will be charged while the state of Kelantan will not impose zakat on gold jewelry even if the gold jewelry exceeds85 grams. Accordingly, the data from the zakat institution websites have clearly provided information on zakat for gold jewelry. The online zakat system has made it easier for Muslims, who have lately been paying attention to how important it is to pay zakat, to calculate the amount of zakat payable, namely, zakat for gold jewelry.